Dinamika Regulasi Otonomi Daerah Di Indonesia Perspektif Siyasah Syar’iyah - Purnama, Muhammad Risam (Sharia Journal and Education Center Publishing, 2025)
Regional autonomy is based on three principles: decentralization, deconcentration, and assistance. This study analyzes several regulations related to the sustainability of regional autonomy in Indonesia. Two key issues in the regulations examined in this study are administrative and fiscal decentralization, marked by the enactment of Law Number 35 of 2020, which grants mining business permits to the central government, a matter previously under the authority of regional governments. Furthermore, the allocation of regional levies and taxes to finance national strategic projects (PSN) is regulated by Government Regulation Number 35 of 2023. At the same time, Presidential Instruction Number 1 of 2025 regulates efficiency for regional governments, followed by Government Regulation Number 38 of 2025 concerning the provision of loans by the central government. This research uses a juridical-normative approach with a siyasah syar'iyah perspective, an Islamic concept that governs regulations pertaining to the authority of the government and other elements. This study concludes that the regulations examined are inconsistent with the concept of decentralized government closer to the people and even have the potential to trigger horizontal and vertical conflict. Given this, this study offers several points regarding strengthening regional autonomy ahead of the revision of Law No. 23 of 2014 concerning Regional Government. Keywords: Regional Autonomy, Administrative and Fiscal Decentralization, Syariah Siyasah.